Impact of the Knowledge Society in the University and in Scientific Communication. - Duart, Josep M.; Mengual-Andrés, Santiago (RELIEVE: Revista Electrónica de Investigación y Evaluación Educativa, 2014)
Over the last two decades as a result of the introduction and intensive use of technologies for information and knowledge in general, from the internet in particular, the university is living in a process of complete transformation that affects it´s academic and organizational structures as well as the conception of educational methodology. The ICTs have demonstrated a need to establish coherent institutional strategies in their use and application along with the possibility to expand the sphere of institutional action in regards massive access to higher education. All of this shows an existing change from a model of education based on the transmission of knowledge, that was rather limited and under restricted access, to another that should fundamentally facilitate the competence to learn from people that live in the world in constant change, with open access to information and knowledge. In addition, all of this implies a transformation in the dynamics of communication and diffusion of scientific knowledge, that is now converted into something open and accessible which is subject to an analysis of knowledge social networks.